Pheochromocytoma: an updated scoping review from clinical presentation to management and treatment - Saavedra T., J. S.; Nati-Castillo, Humberto Alejandro; Valderrama Cometa, L. A.; Rivera-Martínez, Wilfredo A.; Asprilla, Josué; Castaño-Giraldo, C. M.; Sánchez S., Leonardo; Heredia-Espín, Mishell; Arias-Intriago, Marlon; Izquierdo-Condoy, Juan S. (Frontiers in Endocrinology, 2024)
Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumors derived from chromaffin cells, with 80-85% originating in the adrenal medulla and 15-20% from extra-adrenal chromaffin tissues (paragangliomas). Approximately 30-40% of PPGLs have a hereditary component, making them one of the most genetically predisposed tumor types. Recent advances in genetic research have classified PPGLs into three molecular clusters: pseudohypoxia-related, kinase-signaling, and WNT-signaling pathway variants. Specifically, the detection of SDHB-related tumors indicates an increased risk of metastatic disease, which may impact decisions regarding functional imaging in patients with high suspicion of metastasis and influence targeted treatment strategies. Diagnosis of PPGLs primarily relies on biochemical testing, measuring catecholamines or their metabolites in plasma or urine. However, molecular testing, functional imaging, and targeted therapies have greatly enhanced diagnostic precision and management. Personalized treatment approaches based on genetic profiling are becoming integral to the clinical management of these tumors. In South American countries like Colombia, functional imaging techniques such as positron emission tomography/computed tomography (PET/CT) with tracers like 18F-DOPA, 18F-fluorodeoxyglucose (18F-FDG), and 68Ga-DOTA-conjugated somatostatin receptor-targeting peptides (68Ga-DOTA-SST) are used to guide follow-up and treatment strategies. Radionuclide therapy with lutetium-177 DOTATATE is employed for patients showing uptake in 68Ga-DOTA-SST PET/CT scans, while access to 131-MIBG therapy remains limited due to high costs and availability. Recent clinical trials have shown promise for systemic therapies such as sunitinib and cabozantinib, offering potential new options for patients with slow or moderate progression of PPGLs. These advancements underscore the potential of personalized and targeted therapies to improve outcomes in this challenging patient population.